Preparation of Poly(methyl methacrylate) Functionalized Carbon Fiber via Reversible Addition-Fragmentation Chain Transfer Polymerization - Xiong, Lei; Li, Xiaofeng; Liang, Hongbo; Huang, Shengmei (Asian Journal of Chemistry, 2013)
We report a novel method for the functionalization of carbon fiber with poly(methyl methacrylate) by using reversible addition-fragmentation chain transfer polymerization. The carbon fiber was first oxidized with a mixture of nitric acid and sulphuric acid (1:3), in order to introduce hydroxyl groups onto the carbon fiber surface. Then the reversible addition-fragmentation chain transfer agents were immobilized onto the surface of carbon fiber by chemical reaction of hydroxyl groups with silane coupling agent containing dithioester groups. Finally, the methyl methacrylate was initiated and propagated on the carbon fiber surface by reversible addition-fragmentation chain transfer. The poly(methyl methacrylate) grafted carbon fiber was characterized by FT-IR, 1H NMR and TGA. The results show that the poly(methyl methacrylate) grafted carbon fiber were synthesized successfully and the graft content could reach 32.4 %.